Automation of sales reporting in a laundry business - Henares, Jennilyn J. (Animo Repository, 2020)
This action research, “Automation of Sales Reporting in a Laundry Business”, addressed the issue of inaccuracy and inefficiency in the preparation of daily sales report at Laundry ni Juan, a laundry business owned by the action researcher. This action research is aimed to achieve increased accuracy and efficiency in the preparation of the daily sales report through elimination of manual processes and the use of automation in sales reporting. The action research is guided by the SDLC (System Development Life Cycle) Waterfall Model in its transition from a manual to an automated system. First cycle covered the intervention made which was automation through the use of a Point-of Sale (POS) System. Cycle 1 discussed the steps to be undertaken in order to completely implement the POS System from requirements gathering to maintenance. The implementation of the POS system in cycle 1 enabled the automation in cash receipting and sales reporting. The end state is reduction time spent on the daily close process, elimination of overtime work, and elimination of data-recording errors. The Second cycle showed how the POS system was further improved from cycle 1. The second cycle continued to reduce, if not eliminate inaccuracies and inefficiencies in sales reporting. In the second cycle of the action research, quality of customer information was improved through setting controls and parameters in the POS system data entry. The implementation of cycle 2 paved way for elimination of multiple customer records and the availability of a reliable and complete customer data.